Webster's New World college dictionary - Neufeldt, Victoria; Guralnik, David B. (David Bernard), 1920-2000. (New York Macmillan, 1996)
Offers hundreds of new words and meanings, including many unique to American English, with thousands of examples of current usage
Php 491.00
Revised edition of: Webster's New World dictionary of American English. 3rd college edition
Donated by Gorriceta-Rojo family
Keywords: English language -- Dictionaries